RANCANG BANGUN AUTOMATIC HAND WASHING STATION DENGAN MENGGUNAKAN MIKROKONTROLLLER ARDUINO UNO R3 - Alfian Djafar; Muhammad Gilang Kentjana; Reza Kristiyanto; Yusuf Afudin (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Kristen Indonesia, 2021)
Washbasin needs to be provided in a place that is generally visited by people. It is necessary to design an automatic hand washing machine to reduce direct contact. This study aims to design and manufacture a simple automatic hand washing device, using a microcontroller and equipped with sensors to regulate the faucets and also regulate the release of the soap dish. This research has 3 stages. The first stage of planning includes the selection of actuators, sensors, and microcontrollers. Second, the manufacture of tools in the form of mechanical manufacture, electrical circuits, and programming. The final stage is testing, responding to tools that will function properly, and monitoring those that still need to be developed. Based on the research, the Automatic Hand Washing Station design tool uses a frame in the form of steel angles with holes SA75 3.75 x 3.75 with binders in the form of Hex Bolt and Nut M10, Arduino Uno R3 Microcontroller, Relay Module, Buck Converter, 2 Infrared Sensors, 5 LEDs, the actuators used are Single pump DC 12V 4.5A, servo motor 9.4 kgf.cm, reservoir with a capacity of 19 liters, and Power Adapter 12V 5A. The electronic system affects the performance of the actuator which results in the less functioning of the actuator itself. This connected obstacle is caused by the condition of the jumper cables that accumulate and also the less than the optimal output power. The programming system uses the Arduino IDE and can run well in the simulation tool process.